Analisis Kebutuhan E-modul Interaktif Terintegrasi STSE (Science, Technology, Society, Environment) pada Materi Larutan Asam Basa sebagai Sumber Belajar Mandiri Siswa SMA/MA - Nabila Ayu Kharisma; Erfan Priyambodo (LPPM Universitas Negeri Jakarta, 2025)
This study aims to analyze the needs of chemistry teachers for the development of integrated interactive e-modules on STSE (Science, Technology, Society, and Environment) regarding acid-base solutions for high school students, which are used as independent learning resources. This study applies a qualitative approach using an exploratory survey method. The research subjects consisted of seven chemistry teachers from three schools in the Yogyakarta area, selected using purposive sampling. Data were collected using a semi-open questionnaire consisting of three main aspects, namely the implementation of chemistry learning, STSE integration, and responses and expectations regarding e-module development. Data analysis was performed applies content analysis techniques through interpretive coding. The results showed that most teachers considered acid-base solution material difficult for students to understand due to the abundance of theory and calculations, as well as the limited learning resources available in the form of textbooks and conventional resources from school facilities. The majority of teachers did not yet understand the STSE approach but showed high enthusiasm for the development of interactive e-modules that are interesting, easy to use, relate to science and technology, and are relevant to everyday life. Thus, the results of this needs analysis confirm that the development of STSE-based interactive e-modules is urgently needed to support more meaningful and contextual chemistry learning, as well as to foster student independence in learning.